Impact of long-term loquat cultivation on rhizosphere soil characteristics and AMF community structure: implications for fertilizer management - Zhang, Yu; Liang, Zhenteng; Zheng, Liangxun; Wang, Xinyang; Chen, Hui; Xu, Tingying; Tang, Ming (Frontiers in Plant Science, 2025)
The role of arbuscular mycorrhizal fungi (AMF) in assisting the growth of different fruit tree species is well-established, yet the impact of loquat cultivation under long-term human management on the rhizosphere soil characteristics and AMF community structure remains unresolved. To address this knowledge gap, we collected roots and soil samples from 20-year-old loquat in a loquat germplasm resources nursery with consistent water and nutrient conditions including one wild species (YS), three pure species (GXQH, MHH, DWX), and four hybrid species (ZJ90, JT, JTH, ZU7). Our analysis revealed that AMF colonization rates ranged from 40.57% to 65.54%, with Glomus (30.72%) and Paraglomus (29.46%) being the dominant genera across all varieties. Paraglomus dominated in pure species, while Glomus prevailed in wild species. YS exhibited the highest AMF richness than cultivars. Significant variations in soil nutrients and enzyme activities in the rhizosphere among different varieties. Total nitrogen (TN) and total potassium (TK) were significantly negatively correlated with relative abundance of AMF genera, suggesting that nitrogen and potassium may reduce AMF abundance. Mantel test showed that total carbon (TC) and soil organic matter (SOM) were the key factors influencing AMF community composition (P<0.01). These nutrients were positively correlated with dominant AMF genus (0.06, R2 = 0.05) but negatively with rare genus such as Ambispora (−0.08, R2 = 0.24). Overall, these findings confirmed that plant varieties or genotypes drive changes in AMF communities and further demonstrated that long-term nutrient enrichment reduces the diversity of loquat rhizosphere AMF communities. These results support the use of AMF biofertilizers and reducing fertilizer application.